Palaeoenvironment and dating of the Early Acheulean localities from the Somme River basin (Northern France): New discoveries from the High Terrace at Abbeville-Carrière Carpentier. (1st October 2016) - Antoine, Pierre; Moncel, Marie-Hélène; Limondin-Lozouet, Nicole; Locht, Jean-Luc; Bahain, Jean-Jacques; Moreno, Davinia; Voinchet, Pierre; Auguste, Patrick; Stoetzel, Emmanuelle; Dabkowski, Julie; Bello, Silvia M.; Parfitt, Simon A.; et al.
Abstract: Dating the earliest human occupations in Western Europe and reconstructing links with climatic and environmental constraints is a central issue in Quaternary studies. Amongst the discovery of Palaeolithic artefacts ascribed to the Early Pleistocene in southeast Britain and central France the Somme Basin, where the Acheulean type-site Amiens Saint-Acheul is located, is a key area for addressing this topic. Research undertaken over the past 20 years on both Quaternary fluvial and loess sequences of this area has provided a unique dataset for the study of the relations between human occupations and environmental variations. Studies based on an interdisciplinary approach combining sedimentology, palaeontology and geochronology have highlighted the impact of the 100 kyrs cycles on terrace formation during the last million years. In this terrace system, the earliest in situ Acheulean settlements known in the 1990s were dated to early MIS 12 (±450 ka), but new field discoveries, at Amiens "Rue du Manège", dated to ± 550 ka, significantly increase the age of the oldest human occupation in the area. In this context, new fieldwork has been undertaken in Abbeville at the Carrière Carpentier site, famous for its White Marl deposit attributed to the Cromerian and in the same terrace level where the former discoveries of "Abbevillian bifaces" were made by d'Ault du Mesnil. This research is based on an interdisciplinary approach, combining sedimentology, paleontology, dating (ESR on quartz and ESR/U-series on teeth) and archaeology. According to the various bio-proxies (molluscs, large vertebrates, small mammals), the White Marl was deposited during the early part of an interglacial phase in an aquatic slow-flowing environment, as emphasized by the development of oncoliths and the presence of fish and aquatic molluscs. The landscape was composed of a mosaic of open bush and forest areas, in which wet and grassy vegetation developed on riverbanks. On the basis of terrace stratigraphy, ESR and ESR/U-series dating results, and biostratigraphic data, the fluvial deposits of the White Marl can be securely attributed to MIS 15. In addition, some Acheulean bifaces were discovered at the base of the slope deposits, directly overlying the fluvial sequence. These artefacts are most likely coeval with the end of MIS 15 or an early stage of MIS 14, between 550 and 500 ka, and represent, together with the artefacts from Amiens "Rue du Manège", the oldest in situ evidence of Acheulean occupation in Northern France. However, no unquestionable artefacts have been discovered in the White Marl or in the underlying gravel layer. These discoveries contribute to the chronology of the earliest evidence of hominin occupations in north-western Europe which may be related to Homo heidelbergensis . Highlights: We report results of multidisciplinary researches on the famous fluvial sequence of Carpentier Quarry at Abbeville, France. New fieldwork has been undertaken on the "White Marl" attributed to a Cromerian Interglacial and the « Abbevillian ». They concern the chronology and the palaeoenvironmental context of the earliest evidence of hominin occupations in NW Europe.